Influência do conhecimento do objetivo de leitura na compreensão leitora e na consciência textual de alunos de 6º ano do ensino fundamental - Borges, Caroline Bernardes (2022)
This thesis, situated within the scope of psycholinguistic studies, has as its general objective to verify the influence of knowing reading objectives, delineated by the instruction of the task, in the production of text retelling, reading comprehension and textual awareness. By means of an empirical research, the performance in the story retelling (reading objective), the reading comprehension scores and the participants’ textual awareness levels were analyzed, as well as the existing correlations between these data, seeking to understand to what extent knowing the reading objectives contributes to reading comprehension and textual awareness, considering intragroup correlations. The sample consisted of 69 sixth graders (four classes) from a public Elementary School situated in the South of Brazil, as well as by the teacher of the classes. The students were randomly distributed according to the research groups: group 1 – knowledge of the task instruction (to prepare a retelling of the text) before reading the text (reading objective before - ROB); and group 2 – knowledge of task instruction after reading the text (reading objective after – ROA). Six instruments were administered: a) text for reading and for elaboration of the retelling, introduced or not by the instruction about the reading objective; b) Reading comprehension and textual awareness test – the content of the text; c) Reading comprehension and textual awareness test – linguistic analysis; d) Questionnaire on reading and writing habits and retelling habits; e) Questionnaire about tasks on reading and writing (retelling) in the classroom (for the teacher). The results indicated that making explicit the reading objectives to students before carrying out the task led to a better performance in retelling among ROB students – 76.67% in comparison with the performance of students in the ROA group – 63.51%. As for the results of reading comprehension and textual awareness, students in the ROB group performed better in Reading Comprehension - Text Content and Textual Awareness - Linguistic Analysis, while the ROA group performed better in Textual Awareness - Text Content and Reading Comprehension - Linguistic Analysis. There was also a positive and significant correlation between all three elements investigated (reading objective (retelling), reading comprehension and textual awareness) in the ROB group, except between Retelling and Reading Comprehension - Text Content, and, in group 2, the correlation was positive and significant among all elements. As for the significant correlations among the three elements of the research axis of this dissertation regarding the ROB group and reading and writing habits and retelling habits, relevant correlations were found: Reading Comprehension - Text Content, with the frequency of library use; as for Textual Awareness – Text Content, with the frequency of writing; Reading Comprehension – Linguistic Analysis with reading frequency; and, as for Textual Awareness – Linguistic Analysis, with the frequency of using the library, and also with the frequency of reading and writing. The significant correlations among reading and writing habits and retelling habits in the ROB group were between the frequency of library use and the frequency of reading; between the frequency of using the library and the frequency of writing; and between the reading and writing frequency. As for the significant correlations between the three elements of the research axis of this dissertation, in the ROA group and reading habits, writing habits and retelling habits, it was observed that: as for Retelling, it was correlated with the frequency of use of the library, with the reading and the writing frequency; as for Reading Comprehension – Linguistic Analysis, the correlations were with prior knowledge of the reading objective; and, as for Textual Awareness – Linguistic Analysis, with the frequency of writing. The significant correlations between the reading writing and retelling habits in the ROA group were between the frequency of library use and the frequency of reading, and between the frequency of reading and the frequency of writing. This study has implications for classroom management and for the literature on the topic, including the importance of the teacher making explicit the reading objectives before the activities and the impact of reading and writing habits on the performance in reading comprehension and textual awareness.